Knowledge of Young Women About Dysmenorrhea in Madrasas Aliyah Ulumul Qur'an Stabat - Nurhikmah Panjaitan (Science Midwifery, 2021)
Dysmenorrhea is pain in the pelvic area due to menstruation and the production of prostaglandin substances, often starting immediately after experiencing the first menstruation (manarche ). The pain decreases after menstruation, but in some women the pain can continue during the menstrual period. This type of research is descriptive with a research design, which aims to determine the knowledge of young women about dysmenorrhea at Madrasah Aliyah Ulumul Qur'an Stabat. The results of a preliminary survey conducted at Madrasah Aliyah Ulumul Qur'an stabat for 3 days obtained data that of 112 teenage girls who had menstruated, 62 of them suffered from dysmenorrhea.